Hubungan Aktivitas Fisik dan Kebugaran Jasmani dengan Kualitas Tidur Lansia - Diah Priyantini; Daviq Ayatulloh (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Introduction: Ageing process is decreasing physical fitness in elderly. Elderly more than 60 year that still have good physical fitness can increase their physiological condition. But, in the fact getting older decrease 30-50% physical fitness, factors that cause are physical activity and sleep quality. This study was aimed to explain correlation between physical activity and sleep quality with physical fitness level in elderly. Methods: This study used correlational descriptive with cross sectional design. The population was elderly that have MMSE score ≥ 17 and barthel index >60. Sample size were 102 respondents with total sampling. Independent variable were physical activity and sleep quality, and dependen variable was physical fitness. Instrument for this research used questionnaire 1x24 hours activity recall and Pittsburgh Sleep Quality Index for independent variable, and for dependent variable use six minutes walking test, five times sit to stand test, chair sit and reach test and body mass index. Data analyze use chi square α ≤ 0,05. Results and Analysis: Results showed that there was significant correlation between physical activity and sleep quality with physical fitness (p = 0,000).  Physical activity that category in moderate until hard and good sleep quality can make elderly’s physical fitness better, because physical fitness was result from metabolism that happened in sleep cycle. Discussion: it can be concluded that physical activity and sleep quality had effect to keep physical fitness, so elderly that lived in elderly care facilities can improve their physical activity and sleep quality to increase physical fitness.